Design and Implementation of an Offline-First Mobile Grocery Arisan Information System Using Flutter and Firebase: Desain dan Implementasi Sistem Informasi Toko Kelontong Seluler Arisan yang Mengutamakan Mode Offline Menggunakan Flutter dan Firebase - Devina; Putri Eli Sandra Hasibuan; Dzikra Azzahra; Adetia Anggriani; Gunawan (FKOM UNIKU, 2026)
Conventional grocery savings schemes (arisan sembako) managed manually often encounter challenges such as inefficient contribution recording, limited transparency, and difficulties in managing participant data. This study aims to design a mobile-based grocery arisan information system to support the digitalization of community-scale grocery savings management. A descriptive research approach was employed, with data collected through observation and interviews conducted at Mila Sembako.The proposed system was designed using Flutter and Firebase and includes system architecture, use case modeling, Firestore database design, and interface mockup, with an offline-first synchronization mechanism to ensure data accessibility under limited or intermittent internet connectivity. The system supports participant management, grocery package management, contribution recording, winner selection, notification services, and cloud-based data synchronization through Firebase. By centralizing data management in a cloud environment, the system enables more efficient record keeping and improved information accessibility for administrators and participants. The resulting system design provides a structured framework for improving the efficiency, transparency, and reliability of grocery arisan management. The study demonstrates the feasibility of utilizing Flutter and Firebase technologies to support the digital transformation of community-based grocery savings schemes and serves as a reference for future system development and implementation